Assessment on the Progress of KCC Scheme in India - Sonia,; D. P. Malik and Joginder Singh Malik, (Indian Journal of Extension Education, 2022)
Financial assistance to agriculture sector is very important as India is an agriculture dominant economy. Government has launched various plans and programmes to boost credit to rural society for supplying requisite quantity of credit to the farmers. Kisan Credit Card scheme was launched in 1998 on recommendations of R.V. Gupta committee. This research paper insights the KCC scheme performance in India since its inception. The main objective was to evaluate the year-wise, agency-wise and region-wise KCCs progress in the country. The period of study was from 1999-00 to 2018-19. The study concludes the growth of Kisan Credit Card scheme both with respect to KCCs issued and sanctioned amount under the scheme during the period 1999-2019. It was also recorded that the performance of Commercial banks was better than the both RRBs and Co-operative banks in implementation of KCC scheme. The study also revealed that inter-region variation in the performance of KCC scheme across the country during 1999-2019.